Emotional Intelligence and Job Engagement of Nurses of Level 1 District Hospitals in Negros Occidental - Jason G. Liansing; Sheila P. Arnibal (Philippine Social Science Journal, 2020)
Emotional Intelligence (EI) has been established as an essential component in success, along with Intelligence Quotient (IQ). Emotional Intelligence is vital in making or maintaining Job Engagement (JE). Dealing with different emotions daily, nurses with low EI are prone to compassion fatigue and job disengagement. Job engagement is essential in ensuring that the quality of care rendered is high, and the patient’s safety is guaranteed. Emotional Intelligence plays a vital role in making sure that nurses have a sense of purpose and, in turn, making them more engaged in their daily duties and responsibilities. Hence, this paper describes the level of Emotional Intelligence and Job Engagement of Nurses in Level 1 District Hospitals in Negros Occidental. Likewise, it explores the relationship between Emotional Intelligence and Job Engagement of nurses’ demographics and the factors that made them stay in the nursing service. Also, it determines the correlation of EI and JE of nurses; and whether EI affects the level of JE.